Audience Responses and Playhouse Epilogues: Staging the Labour of Early Commercial Drama, 1578 – 1625 - Caldicott, Joshua Merlin (2023)
In the final moments of a play, between its conclusion and the judgement it receives, early modern playing companies deployed the epilogue as a device to elicit and consolidate a positive response from its audience. As theatre became a commercial enterprise with the construction of the first permanent playhouses, positive audience responses became crucial to ensuring continued custom through repeat attendance or the encouragement of others to attend. Following the extensive collation and analysis of all 119 extant epilogue texts from 1578 to 1625, this thesis presents the most thorough understanding to date of what occurs during the liminal moment of transition between the play-world and the world of a judging audience. The direct and immediate appeals made by the epilogue to the audience offer an insight into the ways in which audiences engaged with drama, revealing how they made meaning from the plays presented to them, how they expressed their opinions about these plays, and what was at risk when they disapproved of the theatre company’s offerings. This thesis further argues that audiences were courted through revelation of the major forms of labour undertaken by the theatre company, including acting and writing, as well as exploring the work that went into the subsequent printing of the extant epilogues. In doing so, this thesis identifies how theatrical labour was either presented or concealed, in order to present a cohesive image of the work of theatre-making for the audience’s approval.